MODEL PERENCANAAN KOMUNIKASI HUMAS POLRES SUKOHARJO DALAM MEMBANGUN CITRA MELALUI INSTAGRAM - kurnia bagus aditya (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2023)
The regional police station (Polres) of Sukoharjo has carried out activities to build effective communication with the public by disseminating information about the Covid-19 vaccine through Instagram. This study aims to explain the application of the public relations communication model of Polres Sukoharjo in building an image with the socialization of the Covid-19 vaccine through Instagram social media. This study used the descriptive qualitative method. Meanwhile, the data collection method used documentation as well as interviews. The results of this study indicate that the Polres Sukoharjo public relations communication model in disseminating information on the Covid-19 vaccine on Instagram used five-step namely research, plan, execute, measure, and report. Besides, the image produced in this activity impressed the public regarding the public relations performance of the Polres Sukoharjo.